2020
DOI: 10.1002/brb3.1771
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and behavioral symptoms in preoperational glioma patients: Is depression, anxiety, and cognitive impairment related to markers of systemic inflammation?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…TNF-α levels may be increased in patients who suffer from depression and is a potential biomarker for diagnosis of depression ( 82 ). In a pre-clinical study based on an animal model, deletion of TNF-α receptors was associated with antidepressant-like effects in behavioural tests compared with the wild-type counterparts ( 83 ). Additionally, a previous study showed that inhibiting the TNF-α signaling pathway may serve as a novel means of investigating how the CNS inflammatory response is associated with depression ( 81 ).…”
Section: Role Of Cytokines In Depression: Mechanism and Treatmentmentioning
confidence: 99%
“…TNF-α levels may be increased in patients who suffer from depression and is a potential biomarker for diagnosis of depression ( 82 ). In a pre-clinical study based on an animal model, deletion of TNF-α receptors was associated with antidepressant-like effects in behavioural tests compared with the wild-type counterparts ( 83 ). Additionally, a previous study showed that inhibiting the TNF-α signaling pathway may serve as a novel means of investigating how the CNS inflammatory response is associated with depression ( 81 ).…”
Section: Role Of Cytokines In Depression: Mechanism and Treatmentmentioning
confidence: 99%
“…After acute ischemic insult, inflammatory cytokines in the ischemic brain will be upregulated from resident brain cells and infiltrating immune cells, which play complex roles in the pathophysiology of cerebral ischemia (9). Previous evidence supports a relationship of cognition impairment, anxiety, and depression with inflammation processes in several diseases (such as coronary heart patients and cancer) (10,15,16). However, few studies have been performed on the potential cognition impairment/anxiety/depression-associated inflammatory cytokines in AIS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, brain tumors can trigger robust local inflammatory responses [ 31 , 32 ]. Systemic elevation of inflammatory markers has also been linked with worsening prognosis in patients with brain tumors [ 33 , 34 ]. Therefore, the presence of these inflammatory mediators in the circulation and cerebrospinal fluid (CSF) might potentiate the risk for suicidality as they have been convincingly shown to be positive correlates of SI.…”
Section: Discussionmentioning
confidence: 99%